(untitled) (Journal of the College of Education for Women, 2019)
The research tackles the monetary policy of the Abassynian state in Baghdad – the center of the Abassynian caliphate in her last days. This age lasts for morethan eight decades . success – sively four caliphates ruled throuyhout these decades. First. ALNaser Ledeen Alah. AL- Daher Be Amer Alah, AL- mustanser Be-Alah then ALmustausem Be-Alah. This caliphate witnessed a sense of release from the boundage of the Salju guian supremqcy which resulted in an interest in coinage of money (Dinarsamd derhem) and engraving it usiny new forms and new weight that reflects the states monetary independence and national sovereignity being an essencial means for treating in the ex– change of trading between people. Caliphat e also made sure of protecting money,s scales from manipulating or cheating by making balances from glass in the form of Dinarand derham to have a stable weignt with out being an object for heat or coldand to avoid unjust with people.